Diabolische Vigilanz Studien zur Inszenierung von Wachsamkeit in Teufelserzählungen des Spätmittelalters und der Frühen Neuzeit - Bockmann, Jörn; Martin, Alena; Michel, Hannah; Struwe-Rohr, Carolin; Waltenberger, Michael (Vigilanzkulturen / Cultures of Vigilance, 2022)
While God looks directly into people's souls as inspector cordium, the relationship of observation between man and the devil appears as an immanent and indirect, lateral and potentially reciprocal one. The contributions in this volume describe how late medieval and early modern stories narratively modeled such constellations of attention, thereby negotiating mechanisms of social control together with forms of vigilant self-observation.